ULTRASONOGRAPHIC FEATURES OF THE REPRODUCTIVE SYSTEM ORGANS IN 16-YEAR-OLD ADOLESCENT GIRLS BORN PREMATURELY (Modern American Journal of Medical and Health Sciences, 2025)
In recent years, an increase in gynecological diseases among adolescent girls has been observed [1]. A history of premature birth may negatively affect the process of sexual maturation and subsequently influence reproductive function. It is well known that preterm infants are more susceptible to illnesses compared to full-term infants [2]. Protecting and strengthening the health of the younger generation is one of the priorities of state demographic policy, emphasizing the importance of preventive measures aimed at reducing chronic diseases and disability [3]. Particular attention should be paid to the assessment of reproductive potential in 15–17-year-old girls, especially the evaluation of ovarian reserve [4].